2019
DOI: 10.1002/jlcr.3752
|View full text |Cite
|
Sign up to set email alerts
|

Fast enzymatic synthesis of n.c.a. 6‐[18F]fluorodopamine (FDA) from n.c.a. 6‐[18F]FDOPA and the fate of 6‐FDOPA and 6‐FDA in neuroblastoma and Caki‐1 cells after their uptake

Abstract: The catecholamine analogue [123I]mIBG has been used for scintigraphic imaging of neuroblastoma since 1984. It is taken up by the noradrenaline transporter (NAT), which is present in most neuroblastoma cells. An alternative imaging method could be PET with 6‐[18F]fluorodopamine, which is also taken up by NAT, but—in contrast to mIBG—also by dopamine transporter (DAT), present in neuroblastoma cells (NAT > DAT). An enzymatic method was established allowing a rapid, quantitative transformation of FDOPA to FDA by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…in the management of neuroendocrine tumors (NETs) [3][4][5]. Several [ 18 F]FDOPA synthesis reports with nucleophilic substitution methods have been developed to overcome the problems that arose with previous electrophilic substitution methods, such as non-regioselectivity, low radiochemical yields, and low molar activity [6][7][8][9][10][11][12][13][14]. Lemaire et al reported a general ve-step synthesis method using a speci c phase transfer catalyst (PTC) that yielded a su cient degree of enantiomeric purity and radiochemical yield to satisfy the recently adopted European Pharmacopeia (EP) speci cations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…in the management of neuroendocrine tumors (NETs) [3][4][5]. Several [ 18 F]FDOPA synthesis reports with nucleophilic substitution methods have been developed to overcome the problems that arose with previous electrophilic substitution methods, such as non-regioselectivity, low radiochemical yields, and low molar activity [6][7][8][9][10][11][12][13][14]. Lemaire et al reported a general ve-step synthesis method using a speci c phase transfer catalyst (PTC) that yielded a su cient degree of enantiomeric purity and radiochemical yield to satisfy the recently adopted European Pharmacopeia (EP) speci cations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of cell and animal models for a detailed pharmacological radiotracer characterization of, eg, 11 C‐labeled azadipeptides, 18 F‐labeled benzylpiperazines or a cyclic uPA‐derived peptide for the urokinase‐type plasminogen activator receptor follows consistently.…”
mentioning
confidence: 99%